Pelatihan Dan Penerapan Manajemen Mutu 5r Bagi Guru Sekolah Kejuruan Melalui Transformasi Gudang Menjadi Ruang Kelas Layak Belajar: Pengabdian - Sayid Bahri Sriwijaya; TB Ade Rahmatullah; Rosdiana; Felycia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The 5R quality management principles (Ringkas, Rapi, Resik, Rawat, Rajin) have proven effective in improving discipline, efficiency, and orderliness in vocational education environments (Kaizen Institute, 2025). This Community Service Program (PKM) aimed to enhance teachers’ competence in applying the 5R principles through training, mentoring, and hands-on implementation by transforming a storage room into a functional classroom. Nationally, the Badan Pusat Statistik (BPS, 2024) reported that 35.66% of vocational classrooms in Indonesia are damaged. The results show improved teacher understanding of the 5R principles through an experiential learning approach and the successful transformation of a previously cluttered and dark storage room into a clean, bright, and functional classroom. The implementation of 5R not only improved the school’s physical facilities but also fostered a collaborative, disciplined, and sustainable work culture within the vocational education environment.